Legalizing Euthanasia : with special reference to Nigerian, Dutch (Netherlands) and Islamic law - Adeniyi, Omipidan Bashiru (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2010)
This study focuses on the legalization of euthanasia and or assisted suicide around the world. It however paid particular attention to the practice under the Dutch (Netherlands) law, being the first country to legalize both euthanasia and assisted suicide in the whole world. It examines the arguments in support and against legalization. In doing this, the work examines the laws of Nigeria, Dutch (Netherlands), and Islam. It reveals that countries with laws on legalization particularly, the Dutch (Netherlands), do not adhere to the provisions of such laws. It thus reveals the danger in not having clearer laws on the concept. The study reveals the inadequacies in the existing laws of Nigeria on euthanasia and assisted suicide. It further shows that those existing legislations are incapable of handling sensitive and controversial issues as euthanasia and or assisted suicide. Therefore, this study proposes and recommends that Nigeria have a separate and comprehensive law to handle and criminalize euthanasia and assisted suicide in the country. It is hoped that when this law comes into force, it will protect terminally-ill persons including babies born with deformities, disabled, aged and vulnerable persons in Nigeria. Finally, the work suggests that the sanctity of life principle, which both the Nigerian and Islamic law preach, remains the only solution to this dangerous concept. The study also encourages palliative and hospice care for the terminally ill persons.